2010
DOI: 10.1080/10408390903042069
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Cranberry Bioactive Compounds

Abstract: There is a growing public interest for the North American cranberry (Vaccinium macrocarpon) as a functional food because of the potential health benefits linked to phytochemical compounds present in the fruit--the anthocyanin pigments, responsible for its brilliant red color, and other secondary plant metabolites (flavonols, flavan-3-ols, proanthocyanidins, and phenolic acid derivatives). Isolation of these phenolic compounds and flavonoids from a sample matrix is a prerequisite to any comprehensive analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 70 publications
2
38
0
2
Order By: Relevance
“…Similar to a previous report , most of the flavonols found were glycosides of quercetin and myrcetin, although moderate amounts of aglycones were observed as well. Our UPLC-ESI-MS data were consistent with previous reports which showed the presence of the measured different classes of phenolic compounds in by-products of cranberry-juice processing [21,22].…”
Section: Figure 2 Uplc-esi-ms Analysis Of Each Fraction Obtained Frosupporting
confidence: 82%
“…Similar to a previous report , most of the flavonols found were glycosides of quercetin and myrcetin, although moderate amounts of aglycones were observed as well. Our UPLC-ESI-MS data were consistent with previous reports which showed the presence of the measured different classes of phenolic compounds in by-products of cranberry-juice processing [21,22].…”
Section: Figure 2 Uplc-esi-ms Analysis Of Each Fraction Obtained Frosupporting
confidence: 82%
“…The identification and concentration phenolic results are presented in Table 2. Structures of these compounds were identified by comparison of their spectral and MS and/or MS/MS data to those reported in previous studies [21,[28][29][30][31].…”
Section: Identification and Quantification Of Phenolic Compounds In Cmentioning
confidence: 99%
“…The fruit and its juice reportedly exhibit various health benefits, including treatment of recurrent urinary tract infections by preventing the adherence of fimbriated Escherichia coli to mucosal surfaces (Foo, Lu, Howell, & Vorsa, 2000), prevention of in vitro co-aggregation between gram-negative bacterial pairs involved in periodontal diseases (Weiss, Lev-Dor, Sharon, & Ofek, 2002), protection against lipoprotein oxidation (Porter, Krueger, Wiebe, Cunningham, & Reed, 2001), anti-hypertensive activity (Reed, 2002), in vitro antibacterial activity (Côté, Caillet, Doyon, Sylvain, & Lacroix, 2010a), and anticancer activity (Kandil et al, 2002). The bioactive components that make up the cranberry juice have been well characterized (Côté, Caillet, Doyon, Sylvain, & Lacroix, 2010b;Lee, Rennaker, & Wrolstad, 2008;Zuo, Wang, & Zhan, 2002). Several studies have shown anthocyanins, proanthocyanidins, and phenolics from cranberries are active components in molecular mechanism behind various health benefits of cranberries (Apostolidis, Kwon, & Shetty, 2008;Guo et al, 2007;Lin, Labbe, & Shetty, 2005;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%